Iterative Approximations for a Class of Generalized Nonexpansive Operators in Banach Spaces - Thabet Abdeljawad; Kifayat Ullah; Junaid Ahmad; Nabil Mlaiki (Discrete Dynamics in Nature and Society)
In this article, we prove some weak and strong convergence theorems for mappings satisfying condition (E) using the AK iterative scheme in the setting of Banach spaces. We offer a new example of mapping with condition (E) in support of our main result. Our results extend and improve many well-known corresponding results of the current literature.